The imitation of coarticulatory timing patterns in consonant clusters for phonotactically familiar and unfamiliar sequences. Issue 1 (24th January 2020) - Pouplier, Marianne; Lentz, Tomas O.; Chitoran, Ioana; Hoole, Philip
This paper investigates to what extent speakers adapt to unfamiliar consonant cluster timing patterns. We exploit naturally occurring consonant overlap differences between German and Georgian speakers' productions to probe the constraints that language-specific patterns put on the flexibility of cluster articulation. We recorded articulography data from Georgian and German speakers imitating CCV clusters as produced by a German and Georgian audio model, respectively. The German participants adapted their relative overlap towards the Georgian audio model to various degrees depending on whether the cluster was phonotactically familiar to them or not. A higher degree of adaptation was observed for clusters phonotactically illegal in German. Phonotactically legal clusters showed only an intermediate degree of articulatory adaptation, even though acoustically these clusters showed a rather strong move towards the Georgian audio model in terms of the aerodynamics of the interconsonantal transition period. Georgian speakers on the other hand failed to adapt to the German audio model articulatorily and acoustically, possibly because the German cluster inventory is a subset of the Georgian inventory. This means that Georgian speakers can draw on native speaker knowledge for all clusters, which is a factor known to constrain imitation. Also language-specific cue weighting effects may partly condition the results.